Heart failure and acute pulmonary edema linked to sepsis: a case report and a short review of literature - Siniscalchi, Carmine; Zardo, Marianna; Cunzi, Davide; Gaibazzi, Nicola; Volpi, Riccardo; Basaglia, Manuela (Acta Biomedica Atenei Parmensis, 2015)
Heart failure is a most dangerous and insidious complication of the septic state. We describe the case of a patient admitted to our department for weakness of all four limbs and fever. During hospitalization the patient developed a septic state that has manifested itself through the development of heart failure with acute pulmonary edema.